Contrast-enhanced mri imaging of atherosclerotic lesions of the aortic wall - A. S. Maksimova; V. E. Babokin; I. L. Bukhovets; E. E. Bobrikova; Yu. V. Rogovskaya; P. I. Lukyanenok; V. Yu. Usov (Атеросклероз, 2014)
Aim of the study. To analyze MR tomographic imaging features of atherosclerotic lesions of the aorta, with a paramagnetic contrast enhancement, in patients with extensive atherosclerosis and old acute myocardial infarction (AMI).